Derivation and Inflection Processes in Arabic: A Morphological Study - Ritonga, Mei Sari; Salsabilla, Salwa; Pasaribu, Ahmad Jaffar (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2025)
This study examines the processes of derivation and inflection in Arabic from a morphological perspective. Derivation and inflection are two main mechanisms in Arabic word formation that have different but complementary functions. This study aims to describe the concept, form, and function of derivation and inflection in the Arabic morphological system. The method used is a literature study with a qualitative approach, through the analysis of national scientific articles relevant to the study of Arabic morphology. The results show that derivation in Arabic functions as a mechanism for forming new lexemes derived from word roots through certain morphological patterns, thus playing an important role in enriching vocabulary and expanding lexical meaning. Meanwhile, inflection serves to mark grammatical categories such as person, number, gender, and time without changing the lexical meaning of the root word. This study confirms that an integrated understanding of derivation and inflection is key to a comprehensive understanding of the Arabic word formation system.